Optimization of naringenin sunscreen cream formula using the simplex lattice design method - Kartikasari, Ayu Lifia Nur; Wibowo, Anisa Devi Kharisma; Kuncahyo, Ilham (Universitas Ahmad Dahlan, 2023)
Naringenin is a pure isolate belonging to a group of flavonoid compounds with pharmacological effects such as anti-inflammatory, anticancer, antiatherogenic, antifibrogenic, and antioxidant properties. The purpose of this study was to determine the effect of variations in the combination of emulator tween 80 and span 80 on physical quality and stability in naringenin sunscreen preparations, obtain the optimum formula composition from emulsifying agents, and activity of naringenin sunscreen cream preparations in terms of their SPF values. The study used Design Expert 7.1.5 software to design the simplex lattice design method. Each formula was tested for the physical properties of the cream to determine dispersal adhesion for 4 weeks. Naringenin sunscreen cream with a combination of emulsifier tween 80 and span 80 in various concentrations gives a significant difference in the physical quality consisting of the parameters of spreadability, adhesion, and viscosity. The optimum formula for naringenin sunscreen cream obtained the proportion of 9% Tween 80 and 5% span 80. Keywords: Naringenin, Simplex Lattice Design, SPF, Sunscreen.